2015
DOI: 10.3389/fmicb.2015.00461
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new focus in antibiotic and drug discovery from the Streptomyces arsenal

Abstract: Emergence of antibiotic resistant pathogens is changing the way scientists look for new antibiotic compounds. This race against the increased prevalence of multi-resistant strains makes it necessary to expedite the search for new compounds with antibiotic activity and to increase the production of the known. Here, we review a variety of new scientific approaches aiming to enhance antibiotic production in Streptomyces. These include: (i) elucidation of the signals that trigger the antibiotic biosynthetic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 88 publications
0
39
0
1
Order By: Relevance
“…The first systems for applying genome editing to streptomycetes will soon accelerate the construction of diverse kinds of mutant 127130 , while the discovery of a CRISPR-Cas system in S. avermitilis may open up new approaches 131 . Along with new strategies for the cloning and deletion of very large segments of Streptomyces DNA, sufficient to encompass almost all antibiotic biosynthetic gene clusters 132, 133 , procedures are in place to exploit the ever-growing numbers of uncharacterised clusters emanating from genome sequencing, along the lines summarised by 134 and 135. Bioinformatic tools have been developed to predict the nature of the products of such clusters 136 .…”
Section: Technological Advancesmentioning
confidence: 99%
“…The first systems for applying genome editing to streptomycetes will soon accelerate the construction of diverse kinds of mutant 127130 , while the discovery of a CRISPR-Cas system in S. avermitilis may open up new approaches 131 . Along with new strategies for the cloning and deletion of very large segments of Streptomyces DNA, sufficient to encompass almost all antibiotic biosynthetic gene clusters 132, 133 , procedures are in place to exploit the ever-growing numbers of uncharacterised clusters emanating from genome sequencing, along the lines summarised by 134 and 135. Bioinformatic tools have been developed to predict the nature of the products of such clusters 136 .…”
Section: Technological Advancesmentioning
confidence: 99%
“…Streptomyces is the major sources of natural products including effective antimicrobials (Chaudhary et al, 2013 ). Antoraz et al ( 2015 ) have summarized advances on drug discovery from Streptomyces arsenal , illustrating different approaches for elicitation of antimicrobials by nutritional and hormonal signals or production of useful antimicrobials by co-culture and in situ culture technologies. The authors have flash-lighted on utility of different synthetic biological and system biological based metabolic engineering techniques for harnessing the biosynthetic capabilities of Streptomyces .…”
mentioning
confidence: 99%
“…Antoraz et al ( 2015 ) indicated that the application of bioinformatics and “-omic” based engineering have important contribution in drug discovery. The key focus of these technologies is production and overproduction of important molecules or their structural/functional diversification for pharmaceutical value.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are aerobic, Gram-positive with a high G+C content, displaying distinct presence of substrate and spore-bearing aerial mycelia and presence of LL-diaminopimelic acid (LL-DAP) with no characteristic sugars in the cell wall (Williams et al, 1983;Embley & Stackebrandt, 1994). Members of the genus Streptomyces are present in various kinds of environments including diverse terrestrial and marine environments and have been recognized for their ability to produce a wide range of secondary metabolites, bioactive compounds and industrially important enzymes (B erdy, 2005;Watve, 2001;Kim & Goodfellow, 2002;Chater et al, 2010;Antoraz et al, 2015;Abdelmohsen et al, 2015). With a large number of reported species it becomes laborious to identify novel strains to prevent reisolation and duplication of species already known.…”
mentioning
confidence: 99%